A Modeling Strategy for the Investigation of the Effect of Mesoscale SST Variability on Atmospheric Dynamics. Issue 7 (1st April 2019) - Jia, Yinglai; Chang, Ping; Szunyogh, Istvan; Saravanan, R.; Bacmeister, Julio T.
Abstract: An efficient modeling strategy is proposed for the investigation of the effect of the sea surface temperature (SST) mesoscale variability on atmospheric dynamics. Two ensembles of numerical simulations are generated with a high‐resolution atmospheric global circulation model coupled to a slab ocean model. The two ensembles differ only in the treatment of the SST data used for the specification of the SST initial conditions and the estimation of the oceanic heat transport: one of the ensembles is generated by retaining, while the other by filtering, the mesoscale SST variability. The effect of mesoscale SST variability is assessed by comparing the two ensembles. The strategy is illustrated by simulation experiments with the Community Earth System Model, with a focus on the processes of the NH midlatitudes. The results suggest that ocean mesoscale variability has a significant effect on the jet streams, large‐scale flow, and midlatitude storm tracks. Key Points: An atmospheric GCM coupled to a slab ocean model can be used to study the effect of mesoscale SST variability on atmospheric dynamics SST mesoscale variability has a significant effect on components of the atmospheric circulation that play roles in S2S predictability